ANALISIS LEMBAGA DAN KURIKULUM PENDIDIKAN DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI SEKTOR PENDIDIKAN - Nabilah Tasyattata Tsuraya; Muhammad Rizal Efendi; Nadhira Asyifa Nuralina; Nadia Aurelia Kencana Asri; Nina Farliana (Sindoro: Cendikia Pendidikan, 2025)
Education has a central role in improving the quality of human resources, ultimately impacting a nation's progress. Educational institutions and curriculum are the two main factors that determine the effectiveness of the learning process and the readiness of graduates to face the challenges of the world of work, especially in the education sector. However, there are still quality disparities between educational institutions and curriculum implementation that can affect the competence of graduates. Therefore, this study aims to analyze how educational institutions and curricula contribute to improving the quality of human resources in the education sector. This research uses a descriptive qualitative method with a case study approach. Data was collected through a literature review from various sources such as journals, articles, and websites. The results show that the sound quality of educational institutions, supported by a relevant and adaptive curriculum, contributes significantly to improving the competence of human resources in the education sector. Implementing a curriculum based on the needs of the education industry, as well as the support of adequate facilities, has proven to produce graduates who are better prepared to face the challenges of the world of work. The benefits of this research are expected to provide insights for educational policymakers in designing a more effective curriculum and encouraging an increase in the standards of educational institutions to produce quality educators.